Post-Socialist Fathers ‘At Home’ and ‘Away from Home’ in ‘Old Europe’: Facing the Challenge through Masculine Identity Talk - Pajumets, Marion; Hearn, Jeff (Studies of Transition States and Societies, 2012)
This article focuses on those Estonian male migrants to ‘Old Europe’1 who spend most of their time in the domestic realm as caring fathers and supportive spouses to their wives, who are meanwhile advancing their transnational careers. In this context, masculine identity talk can be understood in terms of strategies employed in response to the challenge to the men’s masculinity that this atypical life choice is likely to entail. Identity is viewed in this article as a processual phenomenon that is relentlessly, although not always deliberately, (re)formulated in discourse, rather than determined by the assigned social roles. Analysis of in-depth interviews reveals that there are varied discourses in use that eﬃ ciently reconstruct the interviewees’ sense of personal signiﬁ cance. Interestingly, men predominantly combine ‘alternative’ discourses (‘caring father’, ‘supportive spouse’, ‘civilised adult’), which potentially undermine Estonian idealised masculinity, with the ‘conservative’ discourses (‘professional man’, ‘well-oﬀ ’), that reinforce the Estonian male norm. Men draw on a range of potentially oppositional and conﬂ icting resources for constructing masculinity, without much reﬂ exive selection from their part. Hence, the discourses men engage in position the men as much as the men appear to consciously position themselves in the discourses. This poststructuralist account of identity is located within a more structural historical context of transition and change in contemporary Europe.